POTENSI ANTIINFLAMASI JUS BUAH BELIMBING (Averrhoa carambola L.) TERHADAP DENATURASI PROTEIN IN VITRO - Farizka Erianti; Dona Marisa; Eko Suhartono (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
Starfruit (Averrhoa carambola L.) is an Asian tree that has been used in traditional medicine. Flavonoids, saponins, and tannins is thought to have antiinflammatory in inhibiting protein denaturation. Protein denaturation is a cause of inflammation. This study aims to determine the antiinflammatory potential of starfruit in inhibiting protein denaturation in vitro. This study is a quasi experimental, using a model reaction between 5 % BSA were heated to form protein denaturation by two groups: the juice as the test group and diclofenac sodium as the standard group, which is divided to a concentration of 10%, 20%, and 30%. Potential inhibition of protein denaturation is known to determine the value of IC50 . The results of this study indicate that the starfruit juice has the IC50 value of 11.896 % (r=0.842), whereas for diclofenac sodium by 11.872 % (r=0.866). Positive r values indicate the existence of a positive relation between concentration and inhibiting protein denaturatiom potential. These results indicate that the starfruit juice as a potential inhibitor of protein denaturation for inflamamatory process in vitro. Keywords: antiinflammatory, Averrhoa carambola L., protein denaturatin